Studies of Aniline and it’s Derivatives on Various Organ Systems: A Mini Review - Kumbhare, Nayan; Dhurvey , Varsha (International Journal of Scientific Research in Biological Sciences, 2025)
Certain chemical pollutants in the environment can change a variety of biological processes. Anilines are widely used in the manufacturing of plants, colours, medications, pesticides, and herbicides. This review aims to highlight the destructive, dangerous and altering effects of aniline on various organisms. We believe that this study will provide helpful information regarding aniline's toxicological research, which will help in the formulation of acceptable guidelines for aniline usage.